Development and validation of work attitude scale for midwives - Garcia, Fe Casillan (Education quarterly.)
This study is focused specifically on work attitudes of Filipino midwives. The country is now faced with a breakdown in the delivery of health and midwifery services unless concerted action is taken by the government and private sectors to study the world of midwives in term of their work attitudes. The midwives' work attitude toward new dimensions in their role will influence the competencies and services they will provide for their patients be it in administration, supervision and other work capabilities.